PENERAPAN KEBIJAKAN KETERBUKAAN INFORMASI PUBLIK DI DINAS KOMUNIKASI INFORMATIKA DAN STATISTIK KABUPATEN ENREKANG - S, Faturrahman; Madani, Muhlis; Abdi, Abdi (Universitas Muhammadiyah Makassar, 2023)
This study aims to determine the application of the Public Information Disclosure Policy at the Department of Communication, Informatics and Statistics, Enrekang Regency. This type of research uses a qualitative method which aims to provide a descriptive description of the application of the Public Information Disclosure Policy at the Department of Communication, Information and Statistics, Enrekang Regency. Data sources consist of primary data obtained through interviews, and secondary data taken from documents, records, reports, and official archives that can be supported by the integrity of primary data. The results of the study indicate that the communication indicator produces answers that are in accordance with existing policies, the second indicator regarding resources shows that it is good, and the third disposition shows that the results are already responsible for its implementation.